The relationship between preeclampsia risk and SENCR rs555172 gene polymorphism and expression: SENCR expression and preeclampsia risk - Saravani, Mohsen; Saeedinia, Mostafa; Zaki-Dizaji, Majid; Ghasemi, Marzieh; Rezaei, Sodabe; Chegini, Hamidreza; Zanganeh, Roya; Kahrizi, Sepehr; Dana, Hasan; Kazemi, Elham; Heidary, Zohreh (Cellular and Molecular Biology, 2024)
Preeclampsia, the more severe manifestation of gestational hypertensive disorders, is a major cause of maternal and perinatal morbidity and mortality worldwide. Genetic polymorphisms in long non-coding RNAs (lncRNAs) are considered as potential genetic preeclampsia. This study aimed to explore the association between SENCR rs555172 SNP and PE risk in healthy pregnant women compared to women with preeclampsia. A total of 140 healthy pregnant women and 130 preeclampsia cases were included in the study. The rs555172 genotype was determined using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), and the expression of the SENCR gene was analyzed in 40 placenta tissue samples from both groups. Various statistical approaches were employed to assess the genotypic and allelic frequencies. The results showed no significant difference in the frequency of the rs555172 polymorphism between healthy pregnant women and those with preeclampsia in terms of the dominant (p=0.82), recessive (p=0.39), and over-dominant (p=0.42) models. Additionally, the analysis of SENCR relative expression revealed no significant difference between the two groups (p=0.48). In conclusion, the LncRNA SENCR rs555172(G/A) seems not associated with an increased risk of Preeclampsia in pregnant women.